Cattura o premura?: una nuova spiegazione di Mc 3,21 - Ognibeni, Bruno (Estudios bíblicos, 2007)
Mk 3:21 is a verse that proves embarrassing to many readers, inasmuch as it seems to attribute to Jesus' relatives the intention of taking custody of him and preventing him from exercising his ministry. A new and original explanation, based on some lexical correspondences with the Greek version of 2 K 4:8, is proposed here. According to this explanation, the intention of Jesus' relatives would be that of urging him to have a meal, withdrawing himself from the crowd who had gathered to listen to him.